2019
DOI: 10.3892/etm.2019.7874
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell‑derived exosomes protect against myocardial infarction by promoting autophagy

Abstract: Exosomes have been demonstrated to be effective in the treatment of a variety of cardiac disorders. However, the effects of mesenchymal stem cell (MSC) exosomes on myocardial infarction is yet to be determined. The current study aimed to investigate the potential therapeutic effects of MSC exosomes on myocardial injuries that are caused by myocardial infarction. MSCs were isolated from rat bone marrow and were used for exosome enrichment using culture medium. Confirmation that MSCs and exosomes had been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…Autophagy is a dynamic process of degradation (Cardinal et al, 2009 ). The protective effect of BMSC-Exos on myocardial I/R injury appears to be closely related to the activation of autophagy (Zou et al, 2019 ), but their mechanism of autophagy in cerebral I/R injury has never been reported. In the current study, both the results of TEM and GFP-RFP-LC3 indicated that there was a large increase in number of autolysosomes in the OGD/R+BMSC-Exos group, further suggesting that BMSC-Exos was involved in the promotion of autophagic flux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is a dynamic process of degradation (Cardinal et al, 2009 ). The protective effect of BMSC-Exos on myocardial I/R injury appears to be closely related to the activation of autophagy (Zou et al, 2019 ), but their mechanism of autophagy in cerebral I/R injury has never been reported. In the current study, both the results of TEM and GFP-RFP-LC3 indicated that there was a large increase in number of autolysosomes in the OGD/R+BMSC-Exos group, further suggesting that BMSC-Exos was involved in the promotion of autophagic flux.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, without any cytological characteristics such as proliferation and differentiation of BMSCs, BMSC-Exos have relatively stable biological characteristics, which reduce the risk of BMSC transplantation and make it possible to replace BMSCs for more effective treatment of cerebral I/R injury. In addition, BMSC-Exos have been shown to protect against myocardial I/R injury and inhibit myocardial infarction pathogenesis by regulating autophagy (Zou et al, 2019 ). Therefore, we hypothesized that BMSC-Exos may have a similar effect in cerebral I/R injury and the mechanism may be related to autophagy and pyroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…MSC-derived EVs are reported to have a therapeutic effect in a broad spectrum of diseases. Beneficial effects in ischemia-reperfusion induced kidney injury [102] and protective properties against myocardial infarction [103]; just two of many examples demonstrating their therapeutic potential. These EVs contain a specific enriched subset of miRNAs [104] and proteins [105], modulating cellular response and triggering tissue repair [106].…”
Section: Foreign Moleculesmentioning
confidence: 99%
“…The main sources are the bone marrow MSCs (BM-MSCs), adipose-derived MSCs (AD-MSCs), and umbilical cord MSCs (UC-MSCs). A large number of studies have investigated the role of MSCs in many diseases, including diabetic retinopathy [12], myocardial infarction [13], diabetes [14], and DN [15][16][17][18][19] in mice and rats. However, the underlying mechanisms of these beneficial effects are not completely elucidated.…”
Section: Introductionmentioning
confidence: 99%